Effect of Pseudomonas putida on Growth and Anthocyanin Pigment in Two Poinsettia (Euphorbia pulcherrima) Cultivars - Ramon Zulueta-Rodriguez; Miguel Victor Cordoba-Matson; Luis Guillermo Hernandez-Montiel; Bernardo Murillo-Amador; Edgar Rueda-Puente; Liliana Lara (The Scientific World Journal)
Pseudomonas putida is plant growth promoting rhizobacteria (PGPR) that have the capacity to improve growth in plants. The purpose of this study was to determine growth and anthocyanin pigmentation of the bracts in two poinsettia Euphorbia pulcherrima cultivars (Prestige and Sonora Marble) using three strains of P. putida, as well as a mixture of the three (MIX). Comparison with the control group indicated for the most part that Prestige grew better than the Sonora Marble cultivars with the PGPR strains. Prestige with the MIX strain grew better compared to control for the number of cyathia (83 versus 70.4), volume of roots (45 versus 35 cm3), number of leaves (78 versus 58), and area of leaf (1,788 versus 1,331 cm2), except for the number of flowers (8.8 versus 11.6). To the naked eye, coloration of plants appeared identical in color compared to the control group. For all plants with P. putida strains, there was less anthocyanin pigment, but biomass was always greater with PGPR strains. Nevertheless, to the naked eye, the coloration of the plants appeared identical in color compared to the control group. This is the first study reporting the positive effects of P. putida rhizobacteria treatments on growth of poinsettia cultivars.